A Slow-Motility Phenotype Caused by Substitutions at Residue Asp31 in the PomA Channel Component of a Sodium-Driven Flagellar Motor - Kojima, Seiji (American Society for Microbiology, 2000)
PomA is thought to be a component of the ion channel in the sodium-driven polar-flagellar motor of Vibrio alginolyticus. We have found that some cysteine substitutions in the periplasmic region of PomA result in a slow-motility phenotype, in which swarming and swimming speeds are reduced even in the presence of high concentrations of NaCl. Most of the mutants showed a sodium ion dependence similar to that of the wild type but with significantly reduced motility at all sodium ion concentrations. By contrast, motility of the D31C mutant showed a sharp dependence on NaCl concentration, with a threshold at 38 mM. The motor of the D31C mutant rotates stably, as monitored by laser dark-field microscopy, suggesting that the mutant PomA protein is assembled normally into the motor complex. Mutational studies of Asp31 suggest that, although this residue is not essential for motor rotation, a negative charge at this position contributes to optimal speed and/or efficiency of the motor.